2021
DOI: 10.1021/acsami.0c20553
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Reduction of N2 Using Metal-Doped Borophene

Abstract: Ammonia synthesis is an essential process in chemistry and industry. However, it is limited by the lack of efficient catalysts and high energy costs. Developing highly efficient systems for ammonia synthesis is an important and long-standing challenge. In this paper, a large class of metal atoms (including 3d/4d transition metals and main group metals) anchored onto borophene have been studied as single atom catalysts for ammonia synthesis. After comprehensive computational screening and systematic evaluation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 60 publications
1
63
0
Order By: Relevance
“…For instance, Yang et al performed the DFT highthroughput screening of catalysts for NRR among a series of transition metal atoms supported on phthalocyanine or borophene monolayer, which provided insights to rational design and explore the efficient and stable NRR catalysts. [403,406] In particular, the NRR reaction (N 2 + 6H + + 6e − → 2NH 3 ) involves several intermediates (*N 2 H, *N 2 H 2 , *N 2 H 3 , *NH 2 , and *N) with two potential reaction pathways (Figure 11b). One is the dissociative pathway, in which the first step is N 2 dissociates into two separate N atoms before the hydrogenation.…”
Section: Nitrogen Reduction Reactionmentioning
confidence: 99%
“…For instance, Yang et al performed the DFT highthroughput screening of catalysts for NRR among a series of transition metal atoms supported on phthalocyanine or borophene monolayer, which provided insights to rational design and explore the efficient and stable NRR catalysts. [403,406] In particular, the NRR reaction (N 2 + 6H + + 6e − → 2NH 3 ) involves several intermediates (*N 2 H, *N 2 H 2 , *N 2 H 3 , *NH 2 , and *N) with two potential reaction pathways (Figure 11b). One is the dissociative pathway, in which the first step is N 2 dissociates into two separate N atoms before the hydrogenation.…”
Section: Nitrogen Reduction Reactionmentioning
confidence: 99%
“…6(c)]. [101][102][103] Xu et al studied the catalytic activity of metal doped borophene towards the CO 2 reduction reaction (CO 2 RR). 104 The results showed that the CO 2 RR was energetically more favorable than the HER on Co-and Pd-doped a-borophene nanosheets because of moderate adsorption energy [Fig.…”
Section: Heteroatom Dopingmentioning
confidence: 99%
“…On the basis of these recent excellent studies, it is clear that 2D boron deserves further research efforts in N 2 fixation and a lot remains to be studied. Very recently, in a theoretical study by Xu et al, [291] the effects of various metal atoms (including 3d/4d transition metals and main group metals) as single atom dopants on 2D borophene Step numbers for the reaction sequences should be referred to (e). Reproduced with permission.…”
Section: Group IIImentioning
confidence: 99%